PENGELOLAAN SUMBER DAYA AIR DI DAERAH KEPULAUAN (Studi Kasus: Kota Ternate Provinsi Maluku Utara) - Ade, Ilham; Rahim, Mustamin; Sultan, Mufti Amir (STABILITA || Jurnal Ilmiah Teknik Sipil, 2023)
An Archipelagic Area Development planning study is a plan to determine the appropriate action process to grow and develop social, economic and environmental ecosystem aspects of the archipelago or group of islands by the capacity of the resources owned by each island. Development planning is intended to make changes towards a better development direction for a community, government, and environment in a certain area by utilizing or utilizing various existing resources and must have an orientation that is comprehensive, complete, and sticks to the ecoregion method.To develop the development of the archipelago area based on water resources.Quantitative research was chosen with the consideration that this research is a problem analysis by researchers; researchers use statistical test tools and secondary data that are quantitative, besides that researchers refer to the theory of water carrying capacity and hydrological theory to study it.Guide researchers to find research problems and then analyze the data using quantitative methods. The results of the study stated that to meet the water needs in the city of Ternate for years to come, a strategy and policy that is environmentally friendly to the community is needed.